... which surpasses all understanding (Phil 4:7) : On the foolishness and beauty of celebrating worship in the dialectics of word and cult - Deeg, Alexander (Stellenbosch Theological Journal, 2019)
Sunday services may be considered as nonsense and a waste of time. The article shows that it is indeed correct to talk about the foolishness of Sunday services and that this is a theologically fitting description for services in which the congregation walks on the ridge between ontological affirmation of God's presence and elimination of the expectation that God may interact with the congregation. Theological insights and literary texts from the early twentieth century (Rilke, Barth, Rosenzweig, Kafka) are connected with a conceptualization of the Sunday service between word and cult - thus presenting an outline of a fundamental liturgy of the Protestant Sunday service.